The political economy of Japan's low fertility - Rosenbluth, Frances McCall (Stanford University Press, 2007)
This study takes an interdisciplinary approach to one of Japan's thorniest public policy issues: why are women increasingly foregoing motherhood? The authors argue that the combination of an inhospitable labour market for women and insufficient support for childcare pushes women toward working harder to promote their careers, to the detriment of childbearing. The book provides policy recommendations for solving not just Japan's fertility issue, but those of other modern democracies facing a similar crisis